Dietary Approach to Stop Hypertension (DASH) Diet, Physical Activity, and Renal Function Among Women with a History of Gestational Diabetes Mellitus. (14th June 2022) - Yang, Jiaxi; Rawal, Shristi; Wu, Jing; Ma, Ronald; Tobias, Deirdre; Chavarro, Jorge; Hu, Frank; Zhang, Cuilin
Abstract: Objectives: To examine individual and joint associations of long-term diet quality and physical activity with sub-clinical measures of renal dysfunction in a longitudinal female cohort with a history of gestational diabetes mellitus (GDM). Methods: This was a retrospective study of women who had reported a physician-diagnosed GDM in the Nurses' Health Study II between 1989–2009. Dietary Approach to Stop Hypertension (DASH) diet score was derived from validated food frequency questionnaires administered every 4 years. Physical activity and other health-related factors were self-reported every 2–4 years. Fasting blood and urine samples were collected in 2012–2014 in a sub-sample (median age: 57 years). Analysis included 646 women who were free of diabetes at the time of biospecimen collection. Renal outcomes included elevated urinary albumin-to-creatinine ratio UACR; ≥20 mg/g) and glomerular hyperfiltration (eGFR ≥95 th percentile [107.3 mL/min/1.73m 2 ]). We used logistic regression to estimate the odds ratios (OR) and 95% confidence intervals (CI) for the associations of habitual diet quality and physical activity with the two subsequently measured renal outcomes, adjusting for major risk factors. Results: Women with a higher DASH score were less likely to have elevated UACR or glomerular hyperfiltration, but the association was only significant for the latter ( p -trend = 0.009; OR for tertile 3 vs. tertile 1: 0.14, 95% CI: 0.03–0.66). No evidence of association was seen for elevated UACR with physical activity. Women who were more physically active (≥150 min/week moderate-intensity or ≥75 min/week vigorous-intensity) had a lower risk of glomerular hyperfiltration (OR = 0.48, 95% CI: 0.23–1.00), compare with those who were less active. Examination of joint associations revealed that women with a higher binary DASH-diet score and higher physical activity had 80% lower risk of glomerular hyperfiltration (OR, 95% CI: 0.20, 0.07–0.54), compared with those who had lower levels of diet quality and physical activity. Conclusions: Our study suggests women with a history of GDM with overall higher diet quality and physical activity have a more favorable renal function profile in midlife. Larger prospective studies in diverse populations are warranted to confirm these findings. Funding Sources: National Institutes of Health, American Diabetes Association.